Dynamic viscosity of colloidal silica suspensions at low and high volume fractions. - Samavat, Siamak; Carrique-Fernández, Félix; Ruiz-Reina, Emilio; Zhang, Wei; Williams, Paul Melvyn (Elsevier, 2018)
A comprehensive study was carried out on the dynamic viscosity of X30 silica dispersions at both high and low volume fractions of colloidal silica particles at various electrolyte ionic strength and pH values. Booth and Ruiz-Reina and Carrique theoretical models (R-R&C) were compared in predicting the primary electroviscous effect (PEE) for viscosity at low volume fractions. To this respect the colloidal dispersion was well characterised with regards to electrolyte properties such as the Debye length, j 1, calculated from the ionic strength, and zeta potential, f, calculated from the electrophoretic mobility using the full numerical model by O’Brien and White (O’B&W). R-R&C hard sphere model (which is a modified version of Simha hard sphere model that includes a boundary condition by Happel on the outer radius of the cell) and the semi-empirical Krieger-Dougherty (K-D) models were fitted to the experimental data at high volume fractions. At both low and high volume fractions the viscosity increased with pH and decreased with ionic strength. At low volume fractions both theoretical models significantly underestimated the experimental dynamic viscosities obtained in this work. This could be attributed to the fuzzy structures for silica particles in aqueous conditions reported previously in the literature, where a significantly larger electroviscous parameter, p, was obtained experimentally for silica particles. At high volume fractions, the R-R&C hard sphere cell model, gave a much better fit to the experimental data compared to the K-D model, which also had the advantage of being only dependent on a coefficient that linearly relates an effective volume fraction postulated for the fuzzy silica particles to the experimental. It is concluded that the R-R&C hard sphere model with the effective volume fraction accounting for the fuzzy structures fits reasonably well the full range of experimental results at low and high volume fractions.
https://openpolicyfinder.jisc.ac.uk/id/publication/13826
Keywords: Sílice; Coloides; Dynamic viscosity; Silica dispersion; Primary electroviscous effect (PEE); Cell model; Core shell model